Return to the city of Joseph : modern Mormonism's contest for the soul of Nauvoo - Esplin, Scott C. (Scott Clair), 1974- (University of Illinois Press, 2019)
'Return to the City of Joseph' examines the conflicts over historical memory that have developed as Mormonism returned to western Illinois. It focuses on the social history of the community, examining interactions between groups impacted by Mormonism's touristic takeover. In a broader way, it also intersects with studies of historical tourism and pilgrimage.